Peroxisome Proliferator-Activated Receptor-α Activation Decreases Mean Arterial Pressure, Plasma Interleukin-6, and COX-2 While Increasing Renal CYP4A Expression in an Acute Model of DOCA-Salt Hypertension. (7th December 2011) - Lee, Dexter L.; Wilson, Justin L.; Duan, Rong; Hudson, Tamaro; El-Marakby, Ahmed
Abstract : Peroxisome proliferator-activated receptor-alpha (PPAR- α ) activation by fenofibrate reduces blood pressure and sodium retention during DOCA-salt hypertension. PPAR- α activation reduces the expression of inflammatory cytokines, such as interleukin-6 (IL-6). Fenofibrate also induces cytochrome P450 4A (CYP4A) and increases 20-hydroxyeicosatetraenoic acid (20-HETE) production. This study tested whether the administration of fenofibrate would reduce blood pressure by attenuating plasma IL-6 and renal expression of cyclooxygenase-2 (COX-2), while increasing expression of renal CYP4A during 7 days of DOCA-salt hypertension. We performed uni-nephrectomy on 12–14 week old male Swiss Webster mice and implanted biotelemetry devices in control, DOCA-salt (1.5 mg/g) treated mice with or without fenofibrate (500 mg/kg/day in corn oil, intragastrically). Fenofibrate significantly decreased mean arterial pressure and plasma IL-6. In kidney homogenates, fenofibrate increased CYP4A and decreased COX-2 expression. There were no differences in renal cytochrome P450, family 2, subfamily c, polypeptide 23 (CYP2C23) and soluble expoxide hydrolase (sEH) expression between the groups. Our results suggest that the blood pressure lowering effect of PPAR- α activation by fenofibrate involves the reduction of plasma IL-6 and COX-2, while increasing CYP4A expression during DOCA-salt hypertension. Our results may also suggest that PPAR- α activation protects the kidney against renal injury via decreased COX-2 expression.